2021
DOI: 10.3390/foods10050918
|View full text |Cite
|
Sign up to set email alerts
|

Application of Date (Phoenix dactylifera L.) Fruit in the Composition of a Novel Snack Bar

Abstract: The aim of the present study was to evaluate the possibilities for using date fruit from the Kingdom of Saudi Arabia in the formulation of a novel snack bar while replacing the used honey with date paste. The technological, textural, microbiological and sensory qualities of the obtained food products were evaluated during storage for 12 days after their production. Date palm fruit in the form of date paste was used as an ingredient in the composition of the new snack bars that also included nuts and dried frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 18 publications
0
29
0
1
Order By: Relevance
“…They showed that the replacement of sucrose in the amount of 50%, the physical, chemical and sensory properties of the bread were similar to the base product, but the calorific value was reduced by 11%. Ibrahim et al [ 30 ] assessed the possibilities of using date fruit in the bar recipe and replacing honey with date paste. With regard to the use of date paste up to 70%, bars with a share of 50% were characterized by the highest overall acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the replacement of sucrose in the amount of 50%, the physical, chemical and sensory properties of the bread were similar to the base product, but the calorific value was reduced by 11%. Ibrahim et al [ 30 ] assessed the possibilities of using date fruit in the bar recipe and replacing honey with date paste. With regard to the use of date paste up to 70%, bars with a share of 50% were characterized by the highest overall acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…The production of snack bars referred to Ibrahim et al (2021) in their research on healthy snack bars that have been modified, namely: 1. Mixing all raw materials according to the formulation in Table 1, until evenly mixed.…”
Section: The Process Of Making Moringa Snack Barsmentioning
confidence: 99%
“…Nowadays, "functional or healthy food" has become a crucial criteria for so many consumers since they demand to have a healthy eating habits and to take high nutritional value from food products (Ibrahim et al, 2021). Achieving both excellent organoleptic characteristics and nutritious composition in a single product could be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving both excellent organoleptic characteristics and nutritious composition in a single product could be challenging. Dates and honey are among the widely used alternative natural substitutes used in snack bar production (Ibrahim et al, 2021). Here, carob-based bar formulations were investigated to see the effect of different kind of gum addition on final product properties.…”
Section: Introductionmentioning
confidence: 99%